Investigating the rheological properties of asphalt binder incorporating different crumb rubber contents based on a response surface methodology - Badri, R.M. (King Saud University, 2020)
The effects of different crumb rubber (CR) contents and their interactions with high temperature ranges on the rheological behavior of asphalt binder were investigated in this study using the response surface methodology (RSM). A temperature sweep test was performed using a dynamic shear rheometer (DSR) on modified binders with 5, 7, 10, 12, and 15 crumb rubber content at temperatures ranging from 46 °C to 82 °C. RSM statistical analysis was conducted based on central composite design (CCD) and assuming the rheological parameters complex modulus (G*) and phase angle (δ°) as response variables. Results from analysis of variance (ANOVA) test indicated that temperature and rubber content affect rheological parameters significantly (p < 0.05). A value of p < 0.0001 indicated a good agreement between the predictions of quadratic models and experimental results with a mean error <5 for all responses. The separate effects of temperature and rubber contents were analyzed, and the results revealed that all responses were influenced by the interaction of both independent variables but were more strongly influenced by rubber content than temperature. Consequently, it can be concluded that RSM is an effective approach for investigating rheological properties. © 2020 The Authors